Genetic insights into PHARC syndrome: identification of a novel frameshift mutation in ABHD12 - Ahmad Daneshi; Masoud Garshasbi; Mohammad Farhadi; Khalil Ghasemi Falavarjani; Mohammad Vafaee-Shahi; Navid Almadani; MohammadSina Zabihi; Mohammad Amin Ghalavand; Masoumeh Falah (BMC, 2023)
Abstract Background Mutations in ABHD12 (OMIM: 613,599) are associated with polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and cataract (PHARC) syndrome (OMIM: 612674), which is a rare autosomal recessive neurodegenerative disease. PHARC syndrome is easily misdiagnosed as other neurologic disorders, such as retinitis pigmentosa, Charcot-Marie-Tooth disease, and Refsum disease, due to phenotype variability and slow progression. This paper presents a novel mutation in ABHD12 in two affected siblings with PHARC syndrome phenotypes. In addition, we summarize genotype-phenotype information of the previously reported patients with ABHD12 mutation. Methods Following a thorough medical evaluation, whole-exome sequencing was done on the proband to look for potential genetic causes. This was followed by confirmation of identified variant in the proband and segregation analysis in the family by Sanger sequencing. The variants were interpreted based on the American College of Medical Genetics and Genomics (ACMG) guidelines. Results A novel pathogenic homozygous frameshift variant, NM_001042472.3:c.601dup, p.(Val201GlyfsTer4), was identified in exon 6 of ABHD12 (ACMG criteria: PVS1 and PM2, PM1, PM4, PP3, and PP4). Through Sanger sequencing, we showed that this variant is co-segregated with the disease in the family. Further medical evaluations confirmed the compatibility of the patients' phenotype with PHARC syndrome. Conclusions Our findings expand the spectrum of mutations in the ABHD12 and emphasize the significance of multidisciplinary diagnostic collaboration among clinicians and geneticists to solve the differential diagnosis of related disorders. Moreover, a summary based on mutations found so far in the ABHD12 gene did not suggest a clear genotype-phenotype correlation for PHARC syndrome.